2020
DOI: 10.1021/acs.joc.0c01412
|View full text |Cite
|
Sign up to set email alerts
|

Azulene Functionalization by Iron-Mediated Addition to a Cyclohexadiene Scaffold

Abstract: The functionalization of azulenes via reaction with cationic η 5 -iron carbonyl diene complexes under mild reaction conditions is demonstrated. A range of azulenes, including derivatives of naturally occurring guaiazulene, were investigated in reactions with three electrophilic iron complexes of varying electronic properties, affording the desired coupling products in 43−98% yield. The products were examined with UV− vis/fluorescence spectroscopy and showed interesting halochromic properties. Decomplexation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The most recent entry in the literature on protonation-dependent fluorescence of azulene was reported by Lewis, Kann and co-workers in 2020 [ 29 ]. They found that 1,3-difunctionalised azulenes 13a – e ( Figure 10 ) protonated upon the addition of TFA, for which a strong turn-on fluorescence response was reported in each instance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent entry in the literature on protonation-dependent fluorescence of azulene was reported by Lewis, Kann and co-workers in 2020 [ 29 ]. They found that 1,3-difunctionalised azulenes 13a – e ( Figure 10 ) protonated upon the addition of TFA, for which a strong turn-on fluorescence response was reported in each instance.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the azulene core has been incorporated into a wide variety of colorimetric chemical probes (exploiting the vivid colours it is famous for) [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], this review will focus on those published probes that exploit the fluorescent nature of azulene. The nature of azulene fluorescence is highly dependent on substitution around the azulene core, which affects whether emission is more dominant from the S 2 or S 1 singlet excited state (a notable exception from this can be found in the work of Zhu et al, who showed that emission of azulene aldehydes can occur from the S 3 or S 2 excited state dependent on the nature of the hydrogen bonding present [ 31 , 32 ]).…”
Section: Introductionmentioning
confidence: 99%
“…S C H E M E 6 9 Synthesis of diastereomeric disubstituted azulenes 167 and 168 and monosubstituted product 169 2.7.1 | Reaction of azulene with cationic 5-iron carbonyl diene complexes Because of its low cost and availability from natural sources, guaiazulene 6 was functionalized as the nucleophile via reaction with cationic 5-iron carbonyl diene complexes 165 as the electrophile under mild reaction conditions, yielding tricarbonyl[methyl 5-(5-isopropyl-3,-8-dimethylazulen-1-yl)cyclohexa-1,3-diene-1-carboxylate] iron 166 in 97% yield (Scheme 68). [107] In an 81% yield, a comparable reaction of azulene 1 with a little excess of complex 165 compared with azulene produced an equimolar mixture of diastereomeric disubstituted azulenes 167 and 168 (Scheme 69).…”
Section: Iron Catalystmentioning
confidence: 99%
“…Optoelectronics, sensors, medicines, and natural product synthesis could all benefit from these azulene derivatives. [107] 2.7.2 | Synthesis of organometallic merocyanines based on the diiron moiety…”
Section: Iron Catalystmentioning
confidence: 99%
“…Both aryl and alkyl substituents on azulene’s seven-membered ring were synthesized from the reaction of substituted pyridinium or pyrylium salts with a cyclopentadienide ion, and aryl and alkyl substituents on azulene’s five-membered ring were prepared from the reaction of tropones bearing a leaving group at the 2-position with activated methylene reagents (Scheme a). In recent years, carbon substituents on azulene have been prepared via transition-metal-catalyzed cross-couplings or C–H activations; however, the amination of azulenes has rarely been reported (Scheme b) . Specifically, amination on the C-1 or C-3 position is even more challenging, because both positions possess more electron density on the electron-rich five-membered ring.…”
mentioning
confidence: 99%